ANALISIS PELAPORAN SPT TAHUNAN 1770 WAJIB PAJAK ORANG PRIBADI PADA KKP JAS - Fauzan Attamimi; Diarany Sucahyati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Taxes act as the main source of state funding obtained from community contributions which can be collected compulsorily without direct compensation. One of the community's obligations is to submit the Annual SPT report. Currently, there are still taxpayers who experience problems in submitting their Annual SPT, especially form 1770. The aim of this research is to find out and analyze the reporting of the 1770 Annual SPT of Individual Taxpayers at the JAS KKP. This research uses descriptive qualitative research methods. The required data was obtained through observation and interview techniques. The results of this research indicate that the complexity of tax regulations is the reason clients use KKP JAS services. The reporting of the 1770 Annual SPT for Individual Taxpayers by KKP JAS has been carried out based on applicable tax regulations. In accordance with the services provided by DJP, KKP JAS uses e-form media. JAS KKP usually reports SPT early to prevent problems that might occur.